Biosafety and antioxidant effects of a beverage containing silymarin and arginine. A pilot, human intervention cross-over trial - Valentová, Kateřina; Vidlář, Aleš; Zatloukalová, Martina; Stuchlík, Milan; Vacek, Jan; Šimánek, Vilím; Ulrichová, Jitka (Food and chemical toxicology, 2013)
The study objective was to investigate the potential of a beverage containing silymarin and L-arginine to alter basic physiological and urodynamic parameters in 22 normal healthy men aged 38-59 years. The volunteers drank 500 ml/day beverage without silymarin and L-arginine for 10 days followed, after a 7-day washout period, by the beverage with 400mg silymarin and 295 mg L-arginine for 10 days. Blood and urine samples were collected on days 0, 10 and 27. The beverages were well-tolerated with no adverse effects. Most of the biochemical, hematological and urodynamic parameters remained unchanged. Total antioxidant capacity, total level of antioxidants, lipoperoxidation products (malondialdehyde), advanced oxidation products of proteins in plasma and glutathione, glutathione peroxidase, glutathione reductase, superoxide dismutase and catalase levels in erythrocytes were not influenced. Serum γ-glutamyl transferase, malondialdehyde level and activity of glutathione S-transferase in erythrocytes were lowered at day 27 and the concentration of total plasma SH-groups was higher on day 10. Using an ex vivo system, we found that silymarin/silybin at 10-100 μM is able to adsorb onto human erythrocytes and the complexes displayed antioxidant properties as studied using ex situ square-wave voltammetry. The trial showed that silymarin in vivo may protect erythrocytes against oxidative damage.
Keywords: dospělí; katalasa; Superoxide Dismutase; Antioxidants; klinické křížové studie; glutathion; Catalase; glutathionperoxidasa; Glutathione; Adult; superoxiddismutasa; erytrocyty; Arginine; Dietary Supplements; Beverages; lidé; nápoje; glutathiontransferasa; Pilot Projects; Glutathione Transferase; pilotní projekty; potravní doplňky; Cross-Over Studies; Glutathione Peroxidase; silibinin; Male; Erythrocytes; Malondialdehyde; silymarin; Silybin; antioxidancia; arginin; malondialdehyd; lidé středního věku; gamma-Glutamyltransferase; mužské pohlaví; Glutathione Reductase; glutathionreduktasa; Middle Aged; gama-glutamyltransferasa; Silymarin; Humans